Analysis of thte significance of technological innovations in business management - Xie Yaoming; E. F. Gulyaeva (Путеводитель предпринимателя, 2021)
This article gives the definition and the essence of the technological innovations within the framework of enterprise level of business management. The innovative business development indicators in terms of technological innovation are presented. Interfering reasons of innovative business development are highlighted. Foreign experience of applying the technological innovations within the business management is analyzed. Innovation development factors are presented in results